The Paradox of Decentralization in Local Innovation Governance: An Analysis of Vertical Regulatory Synchronization in Serdang Bedagai Regency - Tiar Abdul Rahmat Pangaribuan; Atikah Rahmi (SIGn Jurnal Hukum, 2026)
Legal certainty is a fundamental prerequisite for implementing decentralized governance, particularly to ensure protection for the apparatus in developing public service innovations. However, regulatory fragmentation often leads to overlapping authority and administrative uncertainty at the local level. This research aims to examine the legal certainty construction of innovation through a vertical synchronization test of Regulation Number 20 of 2021, and to evaluate its sociological implications on the fluctuation of regional innovation performance. This research employs a normative legal method calibrated with policy evaluation through statutory and conceptual approaches, and analyzes Regional Innovation Index data for the 2020 to 2025 period. The analysis results indicate that the Regent Regulation suffered multilayered substantive defects over time. In the initial formulation phase, the budget deprivation threat sanction for innovations deemed unsuccessful contradicted the apparatus protection principle under Law Number 23 of 2014. Furthermore, the local government has been found to have committed legislative omission by failing to amend the Regent Regulation to accommodate the updates to the institutionalization obligation and affirmative financing guarantees mandated following the promulgation of Ministerial Regulation Number 91 of 2021 and Governor Regulation Number 3 of 2022. Factual evidence confirms that this static and defective legal formulation triggered a climate of bureaucratic fear, resulting in a drastic decline in the regional innovation score in the first year of the regulation’s implementation and subsequent stagnation. In conclusion, punitive innovation regulations that are unresponsive to hierarchical updates have degraded the essence of regional autonomy and created a governance paradox. Therefore, the revocation of the administrative sanction clause and the execution of the institutionalization amendment must be executed to restore a safe authorizing environment for experimental legislation.